Gingersnap - Giff, Patricia Reilly (New York : Wendy Lamb Books, 2013)
When her brother Rob, a Navy cook, goes missing in action during World War II, Jayna, desperate for family, leaves upstate New York and their cranky landlady, accompanied by a turtle and a ghost, to seek their grandmother, who Rob believes may live in Brooklyn. Includes soup recipes.
"A Junior Library Guild selection"--Jkt. flap.
Gr. 3-5
Keywords: Brothers and sisters -- Fiction; Family life -- New York (State) -- Fiction; Orphans -- Fiction; World War, 1939-1945 -- Fiction; Cooking -- Fiction; Missing in action -- Fiction; Ghosts -- Fiction; JUVENILE FICTION / Historical / General; New York (State) -- History -- 20th century -- Fiction